Rothe time-discretization method for Nolinear Parabolic Problems - Elharrar, N.; Igbida, J.; Talibi, H. (Methods of Functional Analysis and Topology, 2022)
In this paper we consider a class of nonlinear parabolic problems whose model is (*) (see pdf-file). Using time discretization technique and Rothe method we prove existence and uniqueness results for bounded weak solutions. Використовуючи техніку дискретизації за часом та метод Рота, доведено існування та єдиність слабкого обмеженого розв’язку для нелінійних параболічних задач вигляду (*).